Black Woman Radicals (BWR) Advocacy Manifesto: Intersectional Feminist Analysis of Afro-Palestinian Layered Oppression - Arina Nihayati; Larasati Larasati; Zhillan Zhalila Fahlevi; Luwemba Musa Maswanku (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
The Israeli-Palestinian conflict has drawn global attention for decades, involving not only states but also international organizations, individuals, and non-governmental organizations. Media coverage often simplifies the conflict as Israeli Defense Force (IDF) vs Hamas or Jews vs Arabs. However, Afro-Palestinian communities face layered oppression that goes underreported—experiencing marginalization both as Black people and as Palestinians. This study aims to analyze how the Black Women Radicals (BWR) movement advocates for Afro-Palestinians through a transnational and intersectional feminist lens. Using an integrative review method, this study systematically examines data such as advocacy manifestos, organizational campaigns, and scholarly articles. Findings show that BWR’s initiatives highlight the intersection of race, nationality, and gender within systems of oppression. Kimberlé Crenshaw’s theory of intersectionality becomes crucial in interpreting BWR’s advocacy as a response to Afro-Palestinians’ structural invisibility and multidimensional subjugation.Konflik Israel dan Palestina telah menjadi perhatian global selama beberapa dekade, melibatkan negara, organisasi internasional, individu, hingga lembaga non-pemerintah. Media kerap membingkai konflik ini secara biner sebagai Israel Defense Force (IDF) melawan Hamas atau Yahudi melawan Arab. Namun, kelompok Afro-Palestina mengalami opresi berlapis yang luput dari pemberitaan utama—sebagai warga Palestina sekaligus ras kulit hitam. Penelitian ini bertujuan untuk menganalisis bagaimana gerakan Black Women Radicals (BWR) melakukan advokasi terhadap Afro-Palestina melalui pendekatan feminisme interseksional dan advokasi transnasional. Menggunakan metode integrative review, studi ini mengkaji berbagai data seperti manifesto advokasi, kampanye organisasi, dan artikel akademik. Temuan menunjukkan bahwa inisiatif BWR menyoroti pertemuan antara ras, kewarganegaraan, dan gender dalam sistem penindasan struktural. Teori interseksionalitas dari Kimberlé Crenshaw penting untuk memahami advokasi BWR sebagai respons terhadap ketaknampakan struktural dan subordinasi multidimensi yang dialami Afro-Palestina.